Cambios de uso del suelo y alteración de paisajes en el Valle de Canal Roya (Prov. Huesca) - Cancer Pomar, Luis Antonio (Geographicalia, 2017)
The traditional territorial and productive organization in the Pyrenees, wich has been preserved with few variations until a few decades ago, centered its activities in certain valleys and alloved large extensions to remain virtually intact. This situation has changed -or, rather, is starting to change- in the last few years as a consequence of the location or planning of plenty of activities with a high physical influence on those hardly altered areas. In this article the case of the Canal Roya valley is analysed, in the Aragonese Pyrenee, a valley where several land developments have been projected wich, were they carried out, would highly modify, among other issues. its current landscape configuration.